Foliar Trichomes Of Some Members Of The Family Acanthaceae And Their Taxonomic Utility - DIPA C; DANIEL M (International Journal of Pharma and Bio Sciences, 2011)
Looking into the importance of micromorphological characters in classification of taxa at various levels and for identifying the important plants even in the absence of floral characters, a preliminary study is conducted in 13 members of the family Acanthaceae. Trichomes were a common feature in the plants screened having located in 11 out of the 13 plants studied. Both glandular and non-glandular trichomes were present. A key based on the trichome characters was prepared to identify the plants bearing them even in the vegetative conditions. These characters can serve as pharmacognostic biomarkers in cases of medicinally important plants.